Estimate a patient’s 10 years cardiovascular risk using the Arteriosclerotic cardiovascular disease tool in a cross-sectional study in Al-Harja, Asser, Saudi Arabia, 2021 - Abdulrhamn Bin Saeed; Bahaa A. Abaalkhail; Ibrahim Ismail; Abdullah Saeed; Saad Al-Khammash (Journal of Family Medicine and Primary Care)
Introduction: Recently, the cases of arteriosclerotic cardiovascular disease (ASCVD) have been increasing in the rural areas of southwest Saudi Arabia. Therefore, this study sought to consider the relevant contributing factors, such as traditional dietary habits and a diet rich in cholesterol and fat, few opportunities for disease screening, false beliefs about chronic disease management medications, delays in diagnosis, and the great distances required for travel to cardiac specialist centers. Methods: A cross-sectional study was conducted at 12 primary health care (PHC) centers, using the ASCVD tool. The total required sample was determined to be 440 participants after calculating based on the total population of Al-Harja. Systematic random sampling was performed using a list of PHC centers and fixed intervals. The study’s outcome is ASCVD risk score divided into four categories: low risk <5%, borderline risk 5%–7.5%, intermediate risk >7.5%–20%, and high risk >20%. Data were collected through interview questionnaires, measurements, and laboratory sample investigations. Result: It was revealed that 16.59% of the participants were classified in the high-risk category for having ASCVD in the next 10 years. There was a significant association between the ASCVD risk score and obesity (P = 0.03). Prior diagnoses for either hypertension or diabetes mellitus (P = 0.00) were significantly associated with an increased ASCVD risk score. Conclusion: An alarmingly high prevalence of high-risk ASCVD scores was seen among male participants, with 54 (22.78%) in the high-risk category, while 19 female participants (9.36%) were in the same category. Therefore, we can conclude that male participants are two times as likely to have a high ASCVD risk than female participants.